MENINGKATKAN LITERASI ANAK-ANAK MELALUI PENDEKATAN KONTEKSTUAL DI KABUPATEN YALIMO, PAPUA - Rosye H.R. Tanjung; Wigati Yektiningtyas; Lisye I. Zebua (JURNAL PENGABDIAN PAPUA, 2020)
A Slogan says that reading is the world’s window. This expression means that through reading someone is able to see and follow the world’s development, including knowledge. Unfortunately, Indonesian reading habit is still low, especially children’s. This also happens in Yalimo Regency, Papua. As relatively new regency, literacy in the area needs to be improved. This community service initiated various literacy activities to motivate children’s literacy: reading, writing, and numeracy. Contextual approach by adopting environment and socio-cultre is used. This community service was conducted for a month on August 2019 in two districts, namely District Elelim and District Abenaho. The result showed that the contextual approach used in learning process drove the children to be more enthusiastic in learning reading, writing and numeracy. Hopefully, this kind activity will be continued by the stakeholders, literacy tutors, and parents to improve literacy in Yalimo Regency. Keywords: contextual literacy, Elelim, Abenahoi,  Yalimo Regency.